The Patient Dignity Inventory: Just another evaluation tool? Experiences with advanced cancer patients. Issue 1 (21st June 2017) - Rullán, María; Arantzamendi, María; Carvajal, Ana; Martínez, Marina; Saenz de Ormijana, Amaia; Centeno, Carlos
ABSTRACT: Objective: The Patient Dignity Inventory (PDI) evaluates sources of distress related to the feeling of loss of dignity and was designed for patients at the end of life. The aim of the present work was to generate a better understanding of the experiences of healthcare staff when using the PDI. Method: An exploratory qualitative study is presented about the experience of 4 professionals who applied the PDI to 124 advanced-cancer patients. Our study consisted of an analysis of their experiences, taken from information generated in a focus group. A thematic analysis was performed on the information generated at that meeting by two researchers working independently. Results: The initial experiences with the PDI on the part of the professionals led them to systematically administer the questionnaire as part of an interview instead of having patients fill it out themselves in written form. What started out as an evaluation very often led to a profound conversation on the meaning of life, dignity, and other sensitive, key issues related to the process of the illness. Significance of results: The PDI has intrinsic therapeutic value and is useful in clinical practice, and it is also a way of examining issues related to dignity and the meaning of life within the context of advanced-stage illness. There is a need for studies that examine patient experiences through a PDI-based interview.